The American Evangelical Christians and the U.S. Middle East policy: A case study of the Christians United for Israel (CUFI) - Salleh, Mohd Afandi (Intellectual discourse, 2012)
This study examines the relationship between religious belief and interest group activism in influencing American foreign policy making by highlighting a group within the American Evangelical Christians namely, Christians United for Israel (CUFI). At present, the organization is actively involved in lobbying for influence over American foreign policy towards the Middle East in general and Israel in particular. This study explores the background and strategies of CUFI, by discussing how its underpinning religious beliefs (notably Eschatology and attitude towards End-Time) provide the basis of support for the state of Israel. It contends that the activism of the organization demonstrates how religious beliefs can constitute a strong factor in motivating lobbying activities for a potential impact on US foreign policy making.